TAXATION OF OTT SERVICES THAT CONDUCT VIRTUAL BUSINESS ACTIVITIES IN INDONESIA - Gazali, Narumi Bungas; Soelistyo, Paulus (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Digitalization in the economic sector provides an opportunity for OTT service business actors to expand their business without spending a large amount of capital considering that the digital economy penetrates space and time so that a paradigm shift in the office or place of business that was originally bad must be physically present. activities virtually via the internet. The proliferation of foreign OTT services in Indonesia has provided a paradigm shift in Permanent Business Entities (BUT) which originally embraced a physical presence to become a digital presence. The collection of PPh & VAT is carried out on foreign OTT services that carry out virtual activities because of the benefits obtained by these foreign OTT services from the Indonesian customs territory. The virtual presence of OTT in Indonesia presents a challenge for the law to be able to act as a social engineering & social control service for modernization in science and technology. The government through PPh26, PMK 48/03/2020, PP 80/2019 has provided further regulations regarding tax collection and value added for foreign OTT services that carry out virtual activities in Indonesia to implement justice and implement resources in national taxation.